2016
DOI: 10.1371/journal.pone.0149121
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Stem Cell to Chondrocyte-Derived Cartilage Matrix in Healthy and Osteoarthritic States in the Presence of Hydroxyapatite Nanoparticles

Abstract: We investigated the effectiveness of integrating tissue engineered cartilage derived from human bone marrow derived stem cells (HBMSCs) to healthy as well as osteoarthritic cartilage mimics using hydroxyapatite (HA) nanoparticles immersed within a hydrogel substrate. Healthy and diseased engineered cartilage from human chondrocytes (cultured in agar gels) were integrated with human bone marrow stem cell (HBMSC)-derived cartilaginous engineered matrix with and without HA, and evaluated after 28 days of growth. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 39 publications
(40 reference statements)
0
23
0
2
Order By: Relevance
“…This close similarity to glycosaminoglycans may account for the success that has been attributed to the use of alginate and agarose in cartilage defect repair applications. In addition, hydrogels exhibit high biocompatibility with cartilage stem cells, low cytotoxicity, and do not undergo hydrolysis through ester bonds. Although they usually take longer to degrade than hydrolysis polymers (e.g., PLGA), they are suitable for cartilage, a slow regeneration tissue .…”
Section: Repairing Damaged Cartilagementioning
confidence: 99%
“…This close similarity to glycosaminoglycans may account for the success that has been attributed to the use of alginate and agarose in cartilage defect repair applications. In addition, hydrogels exhibit high biocompatibility with cartilage stem cells, low cytotoxicity, and do not undergo hydrolysis through ester bonds. Although they usually take longer to degrade than hydrolysis polymers (e.g., PLGA), they are suitable for cartilage, a slow regeneration tissue .…”
Section: Repairing Damaged Cartilagementioning
confidence: 99%
“…Tissue engineering of articular cartilage involves the process of articular chondrocytes isolation, followed by cell seeding on biocompatible matrices or scaffold, cell cultures and subsequent implantation of injured knees (Langer & Vacanti 1993). Various scaffolds have been successfully developed using natural or synthetic polymers and extensively studied in vitro and in vivo for cartilage tissue engineering (Dimida et al 2017;Dua et al 2016;Khorsand-Ghayeni et al 2016;Wang et al 2017). Important aspects such as the function, structure and organization need to be emphasized while constructing the scaffold for therapeutic applications.…”
Section: Introductionmentioning
confidence: 99%
“…Cell sources are an important factor in tissue engineering. To date, the usage of bone marrow mesenchymal stem cells (BMSCs) are extensively tested to develop treatment for cartilage injuries (Dua et al 2016;Nazempour & Van Wie 2016). Various studies have reported that BMSCs potentially support the regeneration of injured cartilage (Pak et al 2016;Ude et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…La mayor parte de estos ensayos se han realizado sobre cartílago rotuliano, pues la patología articular es más frecuente a este nivel. Sin embargo, pese a los esfuerzos realizados hasta la fecha, la solución ideal aún parece lejos de llegar a la realidad clínica (13). Se han ensayado diversas matrices biodegradables con la finalidad de ser implantadas en la zona del defecto y favorecer el proceso de reparación condral (14,15).…”
Section: Introductionunclassified
“…En este contexto, actualmente han cobrado gran importancia los hidrogeles inyectables, especialmente los que incorporan nanopartículas de hidroxiapatita (nHA), pues potencian la integración del constructo condral a la matriz ósea (16,17). En este sentido, el papel de la hidroxiapatita parece fundamental, hasta tal punto que algunos autores han propuesto utilizarla incluso para favorecer la integración cartílago-cartílago (en contenidos inferiores al 1%) (13,17).…”
Section: Introductionunclassified